Analysis of iridium‐augmented GPS positioning performance. Issue 20 (20th September 2019) - Xiao, Liu; Lei, Zhang
Abstract : Although the global positioning system (GPS) has a series of advantages such as global and high precision, there are still many deficiencies, in many cases, GSP cannot meet the requirements of the positioning accuracy. The iridium system is a low‐orbit satellite system with a series of advantages such as global coverage, rapid geometric change, and low propagation loss, which can be combined with the GPS system to achieve the enhancement of positioning accuracy. In this study, the localisation performance of GPS system and iridium‐augmented GPS system is compared using the localisation algorithm based on weighted least‐squares method. The dilution of precision (DOP) values of the GPS system and the iridium‐augmented GPS (iGPS) system and the positioning results before and after the iridium enhancement are calculated. The simulation results show that the iridium augment can optimise the DOP value of the GPS system, reduce the DOP value, and at the same time, when the GPS system cannot get the positioning result, a relatively accurate positioning result can still be obtained through the iridium augment, when the GPS system can get the positioning result, the iridium augment can significantly reduce the positioning error, and can makes the positioning result more accurate.